Who's Missing in the Research on Young Adult Relationships? - Gilbertson, Jordan; Woehler, Nerissa (My University, 2015)
A great deal of research is conducted on young adults' attitudes and behaviors regarding romantic and sexual relationships. We aim to learn more about college students who participate in faith-based student organizations and compare their perspective to other students. In addition, we examine in what ways men's and women's attitudes and behaviors differ.
Color poster with text, photographs, graphs, and tables.
Keywords: Religious students; Young adults; Relationships; Posters